LA COMMUNICATION D’AFFAIRES : DE LA LETTRE COMMERCIALE AU COURRIEL ET AUX PLATEFORMES / THE BUSINESS COMMUNICATION : FROM BUSINESS LETTERS TO EMAILS AND PLATFORMS - Andra-Teodora PORUMB; Adina SĂCARA-ONIŢA (Oradea Journal of Business and Economics)
Written communication has always been essential in a business environment, with written documents holding undeniable legal value. In the context of technological changes over the last 30 years and the rapid development of the Internet, digital communication has gradually replaced traditional means of communication. We have moved from transmitting information through official letters to fax and then to email. In the past, a small number of individuals with specialized training were responsible for drafting business letters, but nowadays, every employee of a company must handle their own correspondence. The shift in devices and the rapid pace at which written communications are drafted and transmitted via the Internet or mobile phones bring about changes in discursive practices. This paper examines email as a discourse genre, first analyzing its differences from traditional correspondence. We then explore its characteristics, particularly its formal flexibility and its grounding in the interactive dynamics specific to digital environments. We also highlight its crucial role in managing professional relationships, facilitating efficient communication, and adapting to contextual needs. Recent business language textbooks propose numerous exercises focusing on understanding professional emails and developing a wide variety of emails while also considering other types of written documents (social media posts, articles for the company’s website). Conceiving professional emails remains a fundamental exercise in business language courses, familiarizing students with the need to communicate with internal colleagues and external partners, thereby improving their skills in written comprehension and expression and better preparing them for integration into the labour market, autonomy, and adaptation to the current business environment.